Considerations for Optimal Blood Pressure Target of Hypertension - Qianhui Ling; Jun Cai (Cardiology Discovery, 2023)
Hypertension is a major risk factor for cardiovascular morbidity and mortality that has led to a huge public health burden. The optimal target of blood pressure (BP) to prevent cardiovascular complications remains unclear. Based on the results of the Systolic BP Intervention Trial (SPRINT) in 2015, the 2017 American College of Cardiology/American Heart Association guidelines for diagnosis and management of high BP in adults has changed the diagnostic threshold from 140/90 to 130/80 mmHg, and the target BP to 130/80 mmHg for nearly all hypertensive patients diagnosed using the new criteria. However, the findings from the SPRINT trial were to an extent contrasting with the results of previous large randomized controlled trials, namely Action to Control Cardiovascular Risk in Diabetes (ACCORD) and Secondary Prevention of Small Subcortical Strokes (SPS3). Besides, the 2018 European Society of Cardiology/European Society of Hypertension guidelines and the 2018 Chinese guidelines have maintained the conventional threshold and recommended target of 140/90 mmHg for most hypertensive patients. Given the special measurement of BP in the SPRINT trial and using an automated measurement system, the intensive systolic BP target of 120 mmHg provided by the SPRINT trial was not widely adopted. Most recently, the Strategy of BP Intervention in the Elderly Hypertensive Patients (STEP) trial, with a higher systolic BP target of 110 to 130 mmHg in the intensive group, confirmed the benefit and safety of intensive BP control in patients with hypertension, in accordance with the SPRINT trial. Here, the results from randomized controlled trials, meta-analyses, and other observational research studies, have been reviewed to evaluate the optimal target of BP treatment and the threshold of diagnostic criteria for hypertension.